2005
DOI: 10.1007/s10038-005-0280-6
|View full text |Cite
|
Sign up to set email alerts
|

Small heat shock protein 27 mutation in a Japanese patient with distal hereditary motor neuropathy

Abstract: Heat shock protein 27 (HSP27) belongs to a family of small heat shock proteins that play significant roles in the cellular stress response and are also involved in the control of protein-protein interactions as chaperons. Mutation in HSP27 has been identified as the cause of axonal Charcot-Marie-Tooth disease (CMT) and distal hereditary motor neuropathy (HMN). Heat shock protein 22 (HSP22) is a molecular counterpart of HSP27, and its mutation is another cause of distal HMN. We screened the mutation of HSP27 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 19 publications
4
62
0
3
Order By: Relevance
“…Another form of DRM arises from a deletion mutation (Q151X) in Bc [236]. Similarly, several other naturally-occurring mutations in the C-terminal region of Hsp27; P182L [229], P182S [237], R140G [238] and K141Q [239] cause distal HMN. Other rarer forms of fibrillar neuropathy have been identified, with deletions in the gene encoding Bc (CRYAB) resulting in the absence of the protein from affected muscle fibres [240].…”
Section: Mutations In the C-terminal Regionmentioning
confidence: 99%
“…Another form of DRM arises from a deletion mutation (Q151X) in Bc [236]. Similarly, several other naturally-occurring mutations in the C-terminal region of Hsp27; P182L [229], P182S [237], R140G [238] and K141Q [239] cause distal HMN. Other rarer forms of fibrillar neuropathy have been identified, with deletions in the gene encoding Bc (CRYAB) resulting in the absence of the protein from affected muscle fibres [240].…”
Section: Mutations In the C-terminal Regionmentioning
confidence: 99%
“…Intriguingly, mutations in K141 of HSPB8 do not disturb its interaction with HSPB1, but rather enhance it, leading to the formation of cytoplasmic aggregates (Fontaine et al 2006;Irobi et al 2004). As for HSP27, numerous mutations predominantly in the a-crystallin domain (R127W, S135F, R136W, T151I) but also in the carboxy-terminal domain (P182L, P182S) have been identified (Evgrafov et al 2004;Kijima et al 2005). Overexpression of mutated HSPB1 variants is sufficient to compromise cell viability, while the S135F mutation has been shown to perturb neurofilament assembly in vitro (Evgrafov .…”
Section: Shsps In Motor Neuropathiesmentioning
confidence: 99%
“…Furthermore, increased HSP27 levels in transgenic HSP27 mice rescue motor neurons and improve neuromuscular function following nerve injury (Sharp et al, 2006). All these studies suggest for a role of HSP27 in the pathogenesis of motor neuron degeneration.We and others identified mutations in HSP27 and its interacting partner HSP22 (small heat shock 22kDa protein 8: gene symbol HSPB8) in another motor neuron disease, distal hereditary motor neuropathy (distal HMN), supporting their pivotal role in motor neuron function Evgrafov et al, 2004;Tang et al, 2005;Kijima et al, 2005). The specific pathomechanism of these mutant small HSPs is unknown, however in vitro studies demonstrated the formation of intracellular aggregates, abnormal assembly of neurofilaments and a disturbance in axonal transport, pathological hallmarks probably triggering motor neuron death in ALS (Evgrafov et al, 2004;Ackerley et al, 2006).…”
mentioning
confidence: 67%
“…The neuroprotective effects of HSP27 may be related to its involvement in neurite extension and branching (Williams et al, 2006). Interestingly, mutations in HSPB1 were found in families with inherited peripheral neuropathies, distal HMN and Charcot-Marie-Tooth disease type 2, in particular (Evgrafov et al, 2004;Tang et al, 2005;Kijima et al, 2005). Although these studies strongly suggest a critical biological role for HSP27 in motor neurons, there is no information about the genetic contribution of HSPB1 to the etiology of the major motor neuron disease, sporadic ALS.…”
Section: Discussionmentioning
confidence: 99%